Digestive problems in rabbit production: moving in the wrong direction? - van der Sluis, Malou; van Zeeland, Yvonne R. A.; de Greef, Karel H. (Frontiers in Veterinary Science, 2024)
Digestive problems, both those with a clear pathogenic origin (e.g., Escherichia coli) and those without obvious pathogen involvement (e.g., syndromes like epizootic rabbit enteropathy (ERE)), are common in production rabbits and account for the majority of losses in meat rabbit production. A multitude of nutritional, genetic and housing factors have been found to play a role in the occurrence of digestive problems. However, the exact early pathophysiological mechanism, including the links between aforementioned risk factors and subsequent development and expression of gastrointestinal disease, is less clear, especially in non-specific enteropathies without obvious pathogen involvement. In this review, we aim to shed more light on the derailment of the normal gastrointestinal functioning in rabbits. We discuss a conceptual integrated view of this derailment, based on an 'overload' pathway and a 'chymus jam' pathway, which may occur simultaneously and interact. The 'overload' pathway centres around exposure to excess amounts of easily fermentable substrate (e.g., starch and protein) that might be incompletely digested prior to entering the caecum. Once there, hyperfermentation may result in changes in caecal pH and inhibition of the normal microflora. The second pathway centres around a chymus jam resulting from a compromised passage rate. Here, reduced hindgut motility (e.g., resulting from stress or limited fibre supply) leads to reduced flow of digesta and increased caecal retention times, which might lead to the production of abnormal caecal fermentation products and subsequent inhibition of the normal microflora. A central role in the presumed mechanism is attributed to the fusus coli. We discuss the suggested mechanisms behind both pathways, as well as the empirical substantiation and alignment between theoretical concepts and observations in practice. The proposed hypotheses may explain the effect of time-based restriction to prevent ERE, which is widely applied in practice but to date not really understood, and suggest that the particle size of fibre may be a key point in the normal functioning of the colon and fusus coli. Further insight into the circumstances leading to the derailment of physiological processes in the rabbit hindgut could provide a meaningful starting point to help improve their gastrointestinal resilience.